مفارقات العنونة ومآلات الدلالة في شعر يحيى الحمادي - عباسي, عبد القادر (جامعة الوادي - University of Eloued, 2023)
ملخص للعنونة ثقلها في الخطاب الشعري ، والحاجة إليها تتجاوز الحدّ الأنطولوجي ، وتعظم فوق شهوة التسمية التي بها ينقل النص من العماء إلى الجلاء ، وتتسامق فيها الرهانات ، إلى حيث تصبح العناوين مناجم للممكنات من الدلالة ، ونصوصا وازنة على صغرها ، تتزاحم فيها الإيحاءات وإن أخذت بنياتها بأشد التقشف ، على أن مطاولة أفق كهذا لا تتهيأ لفعل العنونة حتى يلتفت إلى ما تشرعه استحالات المفارقة من مصاريع الممكن ، وما تتيحه من بدائل مبتكرة للقول ، وحتى يستصحب منطقها المتسلل واستراتيجيتها الكيدية في استدراج القارئ المنتج ، وقد كشف الشاعر اليمني يحيى الحمادي عن جهد لافت حري بالدرس ، وهو ينحت عناوينه من رخام المفارقة ، بل من دخانها ، ويمضي بالقارئ إلى مفترق دلالي لعل هذا المقال أن يوفق في الوقوف على جلية أمره . Abstract: Addressing has its weight in poetic discourse, and the need for it exceeds the ontological limit, and magnifies above the lust of naming with which the text is transferred from blindness to clarity, and the stakes are tolerated, to where the titles become mines of the possible signification, and texts that weigh their smallness, in which the suggestions are crowded, even if their structures are taken with the most austerity, provided that the extension of such a horizon is not prepared for the act of addressing until it pays attention to what the impossibility of paradox legislates from the shutters of the possible, and what it allows from Innovative alternatives to say, and even accompany its logic infiltrator and malicious strategy in luring the reader product, has revealed the Yemeni poet Yahya Hammadi for a remarkable effort should be lesson, as he carves his titles from the marble of paradox, but from its smoke, and moves the reader to a semantic crossroads Perhaps this article will succeed in standing on the clear of his order .
Article
Keywords: المفارقة؛ العنونة؛ يحيى حمادي؛ الدلالة؛ التأويل